FAO Mediterranean Development Project; the integrated development of Mediterranean agriculture and forestry in relation to economic growth, a study and proposals for action. a study and proposals for action (Rome Food and Agriculture Organization of the United Nations, 1959)
This FAO report gives a detailed statistical picture of a major underdeveloped area, together with a wide range of recommendations for speeding up economic growth. The Mediterranean region, embracing all or part of eight southern European countries, the Near-East, and northern Africa, is particularly deserving of study not only because it was the cradle of western civilization, but also because of the great contrast in level of living and productivity with the more advanced western European countries right next door. Although income per capita in this area ($190) is three times as great as that of southern Asia or central Africa, it is only one-fourth that of western Europe, and one-tenth that of the U.S.
lje 04/07/17
Loans
Keywords: Agriculture; Forestry; Economic growth